Factors affecting cervical cancer screening uptake, visual inspection with acetic acid positivity and its predictors among women attending cervical cancer screening service in Addis Ababa, Ethiopia - Atalay Mulu Fentie; Tamir Birhanu Tadesse; Gebremedhin Beedemariam Gebretekle (BMC, 2020)
Abstract Background Cervical cancer is the second most common cancer in Ethiopia next to breast cancer. Despite the high burden of the disease and availability of free screening services in Ethiopia, uptake is still trivial. This study aims to identify factors associated with cervical cancer screening uptake, VIA (visual inspection with acetic acid) positivity and its predictors among women attending cervical cancer screening service in Addis Ababa, Ethiopia. Methods Concurrent mixed study approach of qualitative interview (n = 15) and cross-sectional study among 844 screened women was conducted from February to July 2018. A multistage sampling technique was employed to recruit survey participants from the selected health facilities while the key informants for an in-depth interview were selected purposively. Descriptive statistics were used to summarize the quantitative data and multivariable logistic regression was employed to explore factors associated with VIA positivity of the cervix among screened women. Qualitative data were analyzed using thematic analysis approach. Results The VIA positivity of the cervix was 10.3%. Mean age of study participants was 35.74 ± 7.6 years and women in the age group of ≥45 years were about > 8 times more likely to have VIA test positive result compared to younger women (≤24 years). Being single (AOR = 3.2, 95%CI: 1.4-7.31), widowed (AOR = 18.6, 95%CI: 3.8-91.2), initiating sexual intercourse early (< 16 years) (AOR = 2.72; 95%CI: 1.65-4.49), and having two or more lifetime sexual partners (AOR = 4.9; 95% CI: 1.31-8.75) were also found to be predictors of being VIA positive. Lack of awareness, inaccessibility of the screening service, cultural beliefs and negative perception towards cancer were found to be the major reasons for low uptake of cervical cancer screening. Conclusion The VIA positivity among screened women in Addis Ababa was found to be moderately low compared to reports in other parts of Ethiopia. Having multiple sexual partners, being older age and initiation of sexual intercourse at an early age were associated with VIA positivity of the cervix. Thus, concerted efforts must be taken to increase accessibility of screening services and improve awareness regarding cervical cancer screening.